RESEARCH OF TRENDS IN DEMAND FOR STEM SKILLS IN THE ECONOMIC SECTOR: ДОСЛІДЖЕННЯ ТРЕНДІВ ПОПИТУ НА STEM-НАВИЧКИ В ЕКОНОМІЧНІЙ ГАЛУЗІ - Zhang, Wen (Physical and Mathematical Education, 2025)
Formulation of the problem. In today’s economy, STEM skills (Science, Technology, Engineering, Mathematics) are becoming essential for data analysis, market modeling, and decision-making. Analyzing the demand for STEM skills is becoming relevant and critically important for understanding future employment, education, and economic development trends. This is because digitalization has covered all spheres of public life – from financial services to production and public administration to social communications. Therefore, analyzing trends in demand for STEM skills in the economic sector becomes relevant. Materials and methods. The study is based on a mixed methodology (qualitative and quantitative data) using open and professional sources: content analysis of vacancies, comparative analysis to compare requirements for candidates, analysis of salary ranges and industry trends, and analysis of the content of educational programs for training economists. We used primary (empirical) and secondary data sources. Results. We found that more than half of the jobs for economists in the EU and the US require at least basic programming skills or AI tools. In Europe and the United States, attention is focused on AI, Machine Learning, and FinTech; in Asian countries (Singapore, Hong Kong), there is a demand for analysts and blockchain specialists. In Ukraine, there is an increase in the need for data analysts for agricultural and IT exports and financial modelers. A comparison of the demand for STEM skills in the economy showed the sectoral features of Ukraine and Europe. Conclusions. Countries that invest in STEM education reap significant benefits in developing high-tech industries. Like other emerging economies, Ukraine must adapt to these trends to keep up. The Ukrainian education system should provide advanced training for economists. Therefore, studying Python + SQL by students and internships in European companies, introducing interdisciplinary courses, and cooperating with the IT sector are considered promising.